Glycoprotein (gp) 96 expression: induced during differentiation of intestinal macrophages but impaired in Crohn's disease. Issue 7 (10th June 2005) - Schreiter, K; Hausmann, M; Spoettl, T; Strauch, U G; Bataille, F; Schoelmerich, J; Herfarth, H; Falk, W; Rogler, G
Abstract : Background: The glycoprotein (gp) 96 links the adaptive with the innate immune system. It is a chaperone with a binding domain for peptides generated by proteasomal degradation. During cellular stress, peptide loaded gp96 can be released and presented to T cells by antigen presenting cells (APCs). Methods: mRNAs from in vitro differentiated macrophages (iv mac) and normal intestinal macrophages (IMACs) were compared by subtractive hybridisation and Affymetrix GeneChip analysis. Differentiation induced expression of gp96 was investigated in the multicellular spheroid (MCS) model . In vivo gp96 protein expression was detected by double labelling immunohistochemistry of human colon and in the CD4 + CD62L + T cell transfer mouse model. Results: Five of 76 clones obtained by subtractive hybridisation revealed >99% sequence homology to gp96. Affymetrix GeneChip analysis confirmed induction of gp96 in IMACs. Gp96 mRNA was detected in IMACs from normal and intestinal bowel disease mucosa. Induction of gp96 protein was observed after seven days in the MCS model of IMAC differentiation. Immunohistochemistry confirmed the presence of gp96 protein in IMACs in normal mucosa as well as in mucosa from patients with ulcerative colitis and diverticulitis. In mucosa from Crohn's disease (CD) patients, gp96 protein was not detectable. In the CD4 + CD62L + T cell transfer mouse model, gp96 was verifiable in non-activated IMACs. Conclusion: Gp96 is induced during differentiation of normal IMACs but is not detected in IMACs in CD mucosa. As gp96 has been described as having a role in tolerance induction, this may be relevant for loss of tolerance against luminal bacteria found in CD patients.